(untitled) (Sains Humanika, 2025)
This study examines the influence of transformational leadership on innovative work behavior among bank employees in Johor. Specifically, it investigates how the dimensions of transformational leadership—idealized influence, intellectual stimulation, inspirational motivation, and individual consideration—affect innovative behavior. A quantitative method was employed using a structured questionnaire distributed to 145 employees across 15 branches of a bank. Results indicated that idealized influence, intellectual stimulation, and inspirational motivation positively and significantly impact innovative work behavior. However, individual consideration showed no significant influence. These findings underscore the importance of transformational leadership in fostering innovation within the banking sector, highlighting the need for leadership development programs that emphasize these critical dimensions. By adopting transformational leadership practices, organizations can enhance employee creativity and innovation, ultimately driving competitiveness and growth.